A case report of hepatic abscesses with soft tissue infection caused by methicillin resistant Staphylococcus aureus in a young child. Issue 50 (December 2017) - Wu, Xia; Ye, Ying-Zi; Wang, Chuan-Qing; Wang, Ai-Min; He, Lei-Yan; Yu, Hui
Abstract: Rationale: Pyogenic hepatic abscess in children is a rare clinical condition. Hepatic abscesses caused by methicillin resistant Staphylococcus aureus are extremely rare. Patient concerns: A 6-year-old boy was referred to a tertiary children's hospital for a 6-day history of right lower abdominal pain and fever. Radiographic findings showed hepatic abscesses and soft tissue abscesses around the left femur. Diagnoses: Bacteriology of blood, hepatic abscesses, and soft tissue abscesses showed methicillin resistant Staphylococcus aureus . Interventions: Our patient received adequate drainage of MRSA abscesses and a complete course of antibiotics. Outcomes: The hepatic abscesses were healed and no recurrence has been founded until now. Lessons: This report describes an extremely rare case of hepatic abscesses with soft tissue infection caused by MRSA. Adequate drainage and appropriate systemic antibiotics should be considered as a standard treatment of MRSA abscesses in order to reduce the mortality rate and improve the quality of life.